Edukasi Fakultas Kehutanan dan Ilmu Lingkungan kepada Siswa SMA/SMK/MAN XII Kabupaten Kolaka untuk Meningkatkan Minat Kuliah - Eka Rahmatiah Tuwu; Ema Hermawati Garusu; Junartin Teke; Wa Ode Hastiani Fahidu; Muhammad Saleh Qadri; Hafidah Nur; Satya Agustina Laksananny; Mariana Zainun (Pakis Journal Institute, 2026)
This community service activity aimed to improve the understanding and interest of twelfth-grade SMA/SMK/MAN students in Kolaka Regency toward the Faculty of Forestry and Environmental Science as an alternative choice for higher education. This activity is based on the still limited information among students regarding educational and career prospects in forestry and environmental fields, despite their important role in supporting sustainable development. The activity was conducted through educational outreach methods, including interactive presentations, discussions, question-and-answer sessions, and dissemination of information related to study programs, scholarship opportunities, and career prospects for graduates. The participants were twelfth-grade students from several senior high schools and vocational schools in Kolaka Regency. The results indicated an increase in students’ understanding of the importance of forestry and environmental sciences, as well as higher motivation to consider the Faculty of Forestry and Environmental Science for undergraduate study. Therefore, this activity was considered effective in encouraging students’ interest in pursuing higher education in forestry and environmental sciences.